Using venous blood gas analysis in the assessment of COPD exacerbations: a prospective cohort study. Issue 3 (1st December 2015) - McKeever, Tricia M; Hearson, Glenn; Housley, Gemma; Reynolds, Catherine; Kinnear, William; Harrison, Tim W; Kelly, Anne-Maree; Shaw, Dominick E
Abstract : Introduction: Identifying acute hypercapnic respiratory failure is crucial in the initial management of acute exacerbations of COPD. Guidelines recommend obtaining arterial blood samples but these are more difficult to obtain than venous. We assessed whether blood gas values derived from venous blood could replace arterial at initial assessment. Methods: Patients requiring hospital treatment for an exacerbation of COPD had paired arterial and venous samples taken. Bland–Altman analyses were performed to assess agreement between arterial and venous pH, CO2 and . The relationship between SpO2 and SaO2 was assessed. The number of attempts and pain scores for each sample were measured. Results: 234 patients were studied. There was good agreement between arterial and venous measures of pH and (mean difference 0.03 and −0.04, limits of agreement −0.05 to 0.11 and −2.90 to 2.82, respectively), and between SaO2 and SpO2 (in patients with an SpO2 of >80%). Arterial sampling required more attempts and was more painful than venous (mean pain score 4 (IQR 2–5) and 1 (IQR 0–2), respectively, p<0.001). Conclusions: Arterial sampling is more difficult and more painful than venous sampling. There is good agreement between pH and values derived from venous and arterial blood, and between pulse oximetry and arterial blood gas oxygen saturations. These agreements could allow the initial assessment of COPD exacerbations to be based on venous blood gas analysis and pulse oximetry, simplifying the care pathway and improving the patient experience.